2022
DOI: 10.3390/healthcare10102063
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis Pneumonia in a Non-Immunocompromised Lung Cancer Patient after Surgery: A Case Report

Abstract: We present the Pneumocystis pneumonia case of a 64-year-old man with no remarkable history except for hypertension, who had not undergone any treatment other than surgery. On postoperative day 7, high-resolution computed tomography findings revealed multifocal ground-glass opacifications with interlobular septal thickening in both lungs; therefore, atypical pneumonia was suspected. Polymerase chain reaction (PCR) test performed after bronchoalveolar lavage was positive for Pneumocystis jirovecii (P jirovecii).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Although this infection is rare, there have been cases reported in the literature. Tae-woo Kim et al reported a similar case of PCP pneumonia in a non-immunocompromised lung cancer patient [ 10 ]. The only difference was that the patient in that case had received surgery for the cancer, rather than radiotherapy as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Although this infection is rare, there have been cases reported in the literature. Tae-woo Kim et al reported a similar case of PCP pneumonia in a non-immunocompromised lung cancer patient [ 10 ]. The only difference was that the patient in that case had received surgery for the cancer, rather than radiotherapy as in our case.…”
Section: Discussionmentioning
confidence: 99%